High‐Performance Zeolitic Hollow‐Fiber Membranes by a Viscosity‐Confined Dry Gel Conversion Process for Gas Separation. Issue 29 (31st May 2022) - Yang, Shaowei; Min, Byunghyun; Fu, Qiang; Jones, Christopher W.; Nair, Sankar
Abstract: Zeolite membranes show great potential for gas and hydrocarbon separations, but high manufacturing cost has been one of the main hurdles in their industrial application. Here we demonstrate a method termed viscosity‐confined dry gel conversion (VCDGC) for zeolite hollow fiber membrane fabrication. We demonstrate in detail the VCDGC synthesis of small‐pore CHA zeolite membranes. Extensive permeation measurements reveal that dry gel‐processed CHA zeolite hollow fiber membranes have excellent gas and hydrocarbon separation characteristics well exceeding or comparable to current membranes. Medium‐pore MFI membranes are also fabricated, and their favorable hydrocarbon separation characteristics indicate the versatility and reliability of the VCDGC method. Abstract : A new approach (viscosity‐confined dry gel conversion, VCDGC) is demonstrated for versatile fabrication of zeolite membranes on inexpensive hollow fibers. VCDGC does not require liquid‐phase hydrothermal processing and is amenable to integration with coating processes. The VCDGC synthesis allows preparation of high‐quality CHA and MFI zeolite type membranes, which showed excellent performance in gas separations.